2022
DOI: 10.1111/aje.12971
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fire frequency on vegetation structure and mammal assemblages in a savannah‐woodland system

Abstract: Fire frequency affects vegetation structure and composition in savannah-woodlands, with the potential indirect consequence of affecting the habitat choice and space use of large mammals. Understanding these responses can assist with the development of appropriate fire management policies to conserve co-existing species with different habitat requirements. In a natural experiment in Majete Wildlife Reserve, Malawi, we compared vegetation composition, woody plant structure and large (>5 kg) mammal assemblages on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 132 publications
0
7
4
Order By: Relevance
“…In contrast to some of our results, Nieman et al. (2022) found that impala, kudu, buffalo, sable, waterbuck and zebra frequent areas that are burnt regularly. This contradicts our finding that impala, waterbuck and buffalo are more likely to be found in areas exposed to less frequent fires.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to some of our results, Nieman et al. (2022) found that impala, kudu, buffalo, sable, waterbuck and zebra frequent areas that are burnt regularly. This contradicts our finding that impala, waterbuck and buffalo are more likely to be found in areas exposed to less frequent fires.…”
Section: Discussioncontrasting
confidence: 99%
“…This contradicts our finding that impala, waterbuck and buffalo are more likely to be found in areas exposed to less frequent fires. Furthermore, Nieman et al (2022) also found no evidence that elephant are affected by fire frequency, while our current study indicates a strong tendency for elephant to make use of seldomly burnt areas (Fig. 3k).…”
Section: Management-related Predictorscontrasting
confidence: 88%
See 3 more Smart Citations